Association of APOE e2 genotype with Alzheimer’s and non-Alzheimer’s neurodegenerative pathologies - Goldberg, Terry E.; Huey, Edward D.; Devanand, D. P. (Nature communications, 2020)
The apolipoprotein E (APOE) gene contains both the major common risk variant for late onset Alzheimer’s disease (AD), e4, and the major neuroprotective variant, e2. Here we examine the association of APOE e2 with multiple neurodegenerative pathologies, leveraging the NACC v. 10 database of 1557 brains that included 130 e2 carriers and 679 e4 carriers in order to examine potential neuroprotective effects. For AD-related pathologies of amyloid plaques and Braak stage, e2 had large and highly significant protective effects contrasted with e3/e3 and e4 carriers with odds ratios of about 0.50 for e3 contrasts and 0.10 for e4 contrasts. When we separately examined e2/e4 carriers, risk for AD pathologies was similar to that of e4 carriers, not e2 carriers. For multiple fronto-temporal lobar pathologies and tauopathies, e2 was not significantly associated with pathology. In sum, we found that e2 was associated with large but circumscribed protective effects. The apolipoprotein E (APOE) gene contains both the major common risk variant associated with clinically diagnosed late onset Alzheimer’s disease (AD), APOE e4, and a neuroprotective variant, APOE e2. Here the authors confirm that the e2 allele is protective against Alzheimer’s disease neuropathologies, but show that it is not protective against other neurodegenerative disorders.